2010
DOI: 10.1136/adc.2009.178483
|View full text |Cite
|
Sign up to set email alerts
|

Empirical treatment of neonatal sepsis: are the current guidelines adequate?

Abstract: Current guidelines for empirical therapy in neonates with sepsis are appropriate. However, gentamicin-based regimens should be used in preference to cefotaxime-based treatments, because of lower levels of susceptibility to cefotaxime and the need to avoid exerting selective pressure for resistance. Surveillance data linked to clinical data should further inform rational antibiotic prescribing in neonatal units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
146
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 29 publications
3
146
1
5
Order By: Relevance
“…A current publication from England showed a slightly higher rate of cephalosporin-resistance of 5% in late onset sepsis (LOS) E. coli strains [10]. The same study showed that 93% of LOS E. coli strains remained susceptible to a combination of amoxicillin and gentamicin.…”
Section: Discussionmentioning
confidence: 56%
“…A current publication from England showed a slightly higher rate of cephalosporin-resistance of 5% in late onset sepsis (LOS) E. coli strains [10]. The same study showed that 93% of LOS E. coli strains remained susceptible to a combination of amoxicillin and gentamicin.…”
Section: Discussionmentioning
confidence: 56%
“…15 Second most commonly used antibiotic in this study was amikacin and 75% of preterm neonates were receiving amikacin. Dose of amikacin should be once every 36 hours in babies less than 32 weeks of gestation and for all other babies dose is once every 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…En recién nacidos con sepsis nosocomial confirmada o altamente probable, la cefazolina no fue inferior a la vancomicina en el logro de un resultado clínico adecuado. 4 L a v a n c o m i c i n a e s u n o d e los antibióticos de elección ante la presunción de sepsis por SCN y otros gérmenes Gram positivos, y se emplea en el tratamiento empírico inicial en sepsis tardía o nosocomial, [5][6][7] habitualmente asociada a un antibiótico de amplio espectro. Su excesivo uso provoca diversos problemas, posibles efectos adversos, mantenimiento prolongado de vías intravenosas y la aparición de resistencia bacteriana, que es el que ha merecido mayor preocupación en la búsqueda de estrategias para reducirla.…”
Section: Introductionunclassified